Highly charged ion impact on graphene leading to the emission of low energy electrons. Issue 20 (January 2020) - Schwestka, J; Niggas, A; Creutzburg, S; Kozubek, R; Madauß, L; Heller, R; Schleberger, M; Facsko, S; Wilhelm, R A; Aumayr, F
Synopsis: Recent experiments found that the neutralisation of highly charged ions interacting with a freestanding single layer of graphene proceeds on a femtosecond time scale. This ultra-fast deexcitation was attributed to Interatomic Coulombic Decay (ICD), a process in which core holes in the projectile are filled by previously captured outer electrons and the energy is transferred to electrons of the surrounding carbon atoms. ICD therefore predicts the emission of many low energy electrons. We now present experimental evidence that e.g. Xe 40+ indeed emits up to 85 electrons with energies below 20 eV.